Local Open Government: Key Issues in Scotland, United Kingdom - Afandi, Syed Agung; Afandi, Muslim; Erdayani, Rizki (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
This study aims to analyze key issues of Scotland's open government. Scotland is a member of the Open Government Partnership (OGP) selected for the Local Government Pilot Program. Qualitative approaches and bibliometric analysis methods were used in this study. The data used were obtained from the Google Scholar database through Publish or Perish with four keywords: “Scotland information access”, “Scotland transparency”, “Scotland participation”, and “Scotland collaboration”. Data selection used Mendeley, while the bibliometric map was obtained using VOSviewer. The findings of this study indicate that open government in Scotland has been able to attract public attention. There are 168 relevant articles, 130 topics, and 20 topic clusters. The main focus topics are: participation, collaboration, development, politics, community, young people, gender, justice, transparency, and freedom of information. Meanwhile, the latest and potential topics include: e-participation, inequality, local authority, infrastructure, gender, capacity, culture, inclusion, Islamophobia, power, network, digital collaboration, elite, and public art. Scotland is currently focused on five open government commitments, including: fiscal openness and transparency; health service development, design, and improvement; empowering government through open data; building stakeholder networks on climate change policy; and supporting participation.